The ideology of democratic Athens institutions, orators and the mythical past - Barbato, Matteo ca. 20./21. Jh (New approaches to Ancient Greek institutional history, 2020)
The debate on Athenian democratic ideology has long been polarised around two extremes. A Marxist tradition views ideology as a cover-up for Athens' internal divisions. Another tradition, sometimes referred to as culturalist, interprets it neutrally as the fixed set of ideas shared by the members of the Athenian community